Analysis of The Effect of Unemployment, Economic Growth and Inflation on Poverty in West Sumatra Province - Ulya Syafitri.J; Zilrahmi; Admi Salma (UNP Journal of Statistics and Data Science, 2025)
Poverty remains a major challenge in West Sumatra, although various efforts have been made to improve community welfare. In this context, it is important to understand the factors that influence poverty levels. Unemployment, economic growth and inflation are several important variables that can have a significant effect on poverty levels. Unemployment is one of the problems that is often associated with poverty. On the other hand, strong economic growth has the potential to reduce poverty levels by creating new job opportunities and increasing people's incomes. However, non-inclusive economic growth can increase social inequality and uneven income distribution, which in the end can worsen poverty. Apart from that, inflation can also affect poverty levels by reducing people's purchasing power, especially those with low incomes. This research aims to analyze the effect of unemployment, economic growth and inflation on poverty levels. The multiple linear regression analysis method is used to test the relationship between the independent variables (unemployment, economic growth and inflation) and the dependent variable (poverty). Based on the research findings, it can be concluded that unemployment, economic growth and inflation contribute to poverty in West Sumatra at 49,35% and the remainder 50,65% is explained by other factors outside the model.The analysis indicates a significant linear influence on unemployment and economic growth on poverty in West Sumatra and there is no significant linear impact of inflation  on poverty in West Sumatra.